Stillbirth, neonatal and maternal mortality among caesarean births in Kenya and Uganda: a register-based prospective cohort study. Issue 4 (6th April 2022) - Ghosh, Rakesh; Santos, Nicole; Butrick, Elizabeth; Wanyoro, Anthony; Waiswa, Peter; Kim, Eliana; Walker, Dilys
Abstract : Objective: To investigate the interaction of risks for adverse maternal and perinatal outcomes (stillbirth, predischarge neonatal and maternal mortality) among caesarean section (CS) compared with vaginal deliveries (VD). Design: Prospective cohort study. Setting: 10 CS-capable facilities in Busoga Region, East-Central Uganda and Migori County, Kenya. Participants: Individual birth data were extracted from maternity registers between October 2016 and April 2019. There were a total of 77 242 livebirths and 3734 stillbirths. Overall, 24% of deliveries were by CS with a range of 9%–49% across facilities. Primary outcome measures: Stillbirth, predischarge neonatal mortality and maternal mortality. Results: The adjusted ORs for stillbirth, predischarge neonatal mortality and maternal mortality after a CS were 1.3 (95% CI 1.1 to 1.6), 1.9 (95% CI 1.6 to 2.2) and 3.3 (95% CI 2.2 to 4.9), respectively, compared with a VD. The association between maternal mortality and CS was 3.9 (95% CI 2.8 to 5.5) when the delivery was a live birth and 1.7 (95% CI 1.0 to 3.0) when it was a stillbirth. Post hoc analyses showed that mothers who received a CS had a lower risk of stillbirth if they were documented as a referral. Conclusion: In this context, CS births were at higher risk for worse outcomes compared with VD. Better understanding of CS use and associated adverse outcomes within the mother–baby dyad is necessary to identify opportunities to improve quality of intrapartum care. Trial registration number: NCT03112018 .